First-principles calculation on electronic properties of zinc oxide by zinc 13air system - Mohamad, Ahmad Azmin; Hassan, Muhammad Syafiq; Yaakob, Muhamad Kamil; Mohamad Taib, Mohamad Fariz; Badrudin, Fadhlul Wafi; Hassan, Oskar Hasdinor; Yahya, Muhd Zu Azhan (Elsevier, 2017)
First-principles calculations are performed to study the electronic properties of zinc oxide (ZnO) formed on an anode after discharging a Zn 13air system. Prior to calculation, the ZnO is characterised by X-ray diffraction using Rietveld refinement. Diffracted patterns proved the formation of single phase ZnO, while Rietveld analysis shows that the ZnO has a hexagonal wurtzite structure with lattice parameters, a= 3.244 and c =5.199 A . Geometry optimisation of the hexagonal wurtzite structure of the ZnO is performed using various exchange 13correlation energy functionals. The local density approximation functional method is used to explain the structure, electronic band structure and density of state properties of hexagonal ZnO. The calculated energy band gap was 0.75 eV while the density of states reveals that the O 2p (the top valence band) and Zn 4s (the bottom conduction band) states domination.